2020
DOI: 10.1007/s00381-020-04608-4
|View full text |Cite
|
Sign up to set email alerts
|

Current concepts in the diagnosis and management of adolescent idiopathic scoliosis

Abstract: Background Adolescent Idiopathic Scoliosis (AIS) is a complex 3D structural disorder of the spine that has a significant impact on a person's physical and emotionalstatus. Thus, efforts have been made to identify the cause of the curvature and improve management outcomes. Aim This comprehensive review looks at the relevant literature surrounding the possible aetio-pathogenesis of AIS, its clinical features, investigations, surgicalmanagement options, and reported surgical outcomes in anterior spinal fusion, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 71 publications
1
49
0
10
Order By: Relevance
“…Bracing is considered for curves between 25° and 45° or 20° and 30° that progress more than 5° in 6 months. [ 1 ] Weinstein et al ., in a multicentric study of 242 AIS patients, observed that 72% of patients treated with bracing reached skeletal maturity without ≥50° curve progression versus 48% who were merely observed. [ 10 ] Surgical correction by means of spinal instrumentation with stabilization is considered in skeletally immature patients with curves of >40° or curves with continuous progression and/or if there are both cosmetic and neurologically protective indications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bracing is considered for curves between 25° and 45° or 20° and 30° that progress more than 5° in 6 months. [ 1 ] Weinstein et al ., in a multicentric study of 242 AIS patients, observed that 72% of patients treated with bracing reached skeletal maturity without ≥50° curve progression versus 48% who were merely observed. [ 10 ] Surgical correction by means of spinal instrumentation with stabilization is considered in skeletally immature patients with curves of >40° or curves with continuous progression and/or if there are both cosmetic and neurologically protective indications.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] Surgical correction by means of spinal instrumentation with stabilization is considered in skeletally immature patients with curves of >40° or curves with continuous progression and/or if there are both cosmetic and neurologically protective indications. [ 1 , 9 ]…”
Section: Discussionmentioning
confidence: 99%
“…The Charleston brace is employed in patients with a single major curve of 25-35 degrees at an apex below T8 and is only worn for 8-10 h during sleep [47]. Nighttime bracing has been suggested to be more effective in those who have a single, correctable thoracolumbar, or lumbar curve [43].…”
Section: Kinesitherapymentioning
confidence: 99%
“…The brace, worn for a minimum of 18 h a day, would seem to provide good scientific evidence; furthermore, manual therapy models, such as myofascial release or spinal manipulation, might be potentially convincing in treating AIS when integrated with other conservative therapies [ 11 ]. Regardless, for subjects with angles greater than 40°, the surgical option should be considered [ 12 ]. Although spinal fusion is the traditional approach, one of the most used today, there is a recent perspective that consists of anchoring the vertebral body as a new technique to provide these adolescents with their range of motion, and therefore, a higher HRQoL [ 13 ].…”
Section: Scoliosismentioning
confidence: 99%